Phytotoxins produced by Pestalotiopsis guepinii, the causal agent of hazelnut twig blight - TÜRKKAN, Muharrem; ANDOLFI, Anna; ZONNO, Maria Chiara; ERPER, Ismail; PERRONE, Carmen; CIMMINO, Alessio; VURRO, Maurizio; EVIDENTE, Antonio (Phytopathologia Mediterranea, 2011)
<!-- [if gte mso 9]> Normal 0 14 false false false IT ZH-TW X-NONE MicrosoftInternetExplorer4 <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --><!--[endif]--> The main lipophilic phytotoxic metabolite was isolated from the culture filtrates of Pestalotiopsis guepinii, the fungus causing twig blight of hazelnut. The metabolite was spectroscopically identified as pestalopyrone, a pentaketide that it was originally identified as a minor toxin produced by Pestalotiopsis oenotherae. The toxic activity of pestalopyrone was compared with that of nectriapyrone, a structurally related monoterpenoid recently isolated from Phomopsis foeniculi, and that of the new dihydro-derivative of nectriapyrone. The high phytotoxic activity of nectriapyrone and its dihydro-derivative on three non host plants, showed that the double bond of the 1-methylpropenyl group at C-6 of the aromatic ring is inessential for its activity, while the much lower activity of pestalopyrone showed that the methyl group at C-3 of the same ring is an important structural feature. The high molecular weight hydrophilic phytotoxins produced by this fungus are reported for the first time.